A review of neosporosis and pathologic findings of Neospora caninum infection in wildlife. Issue 2 (August 2015) - Donahoe, Shannon L.; Lindsay, Scott A.; Krockenberger, Mark; Phalen, David; Šlapeta, Jan
Highlights The importance of Neospora caninum-associated disease in wildlife is reviewed. There are only 12 reports of clinical neosporosis in wildlife species to date. The best practice guidelines to follow for reporting wildlife cases of neosporosis are presented.